"Fighting for life and losing": Intensive Care Unit Nursing Staff's Experience With COVID-19 Patient Deaths During the First Two Waves: A Qualitative Study. (May 2022) - Green, Gizell; Gendler, Yulia; Sharon, Cochava
The study explored the experiences of intensive care unit nursing staff caring for COVID-19 patients who eventually died during the two first pandemic waves. We used - descriptive-qualitative-phenomenological. The findings included four main themes—the first vs the second COVID-19 waves, fighting for life and being unable to win, a chronicle of pre-determined death, and nurse's emotional coping with patient death. Based on these findings, we have concluded that in order to enhance nurses' mental health, policy makers and governments need to create an appropriate support system for them.